MLO Differentially Regulates Barley Root Colonization by Beneficial Endophytic and Mycorrhizal Fungi - Hilbert, Magdalena; Novero, Mara; Rovenich, Hanna; Mari, Stéphane; Grimm, Carolin; Bonfante, Paola; Zuccaro, Alga (Frontiers in Plant Science, 2020)
Loss-of-function alleles of MLO (Mildew Resistance Locus O) confer broad-spectrum resistance to foliar infections by powdery mildew pathogens. Like pathogens, microbes that establish mutually beneficial relationships with their plant hosts, trigger the induction of some defense responses. Initially, barley colonization by the root endophyte Serendipita indica (syn. Piriformospora indica) is associated with enhanced defense gene expression and the formation of papillae at sites of hyphal penetration attempts. This phenotype is reminiscent of mlo-conditioned immunity in barley leaf tissue and raises the question whether MLO plays a regulatory role in the establishment of beneficial interactions. Here we show that S. indica colonization was significantly reduced in plants carrying mlo mutations compared to wild type controls. The reduction in fungal biomass was associated with the enhanced formation of papillae. Moreover, epidermal cells of S. indica-treated mlo plants displayed an early accumulation of iron in the epidermal layer suggesting increased basal defense activation in the barley mutant background. Correspondingly, the induction of host cell death during later colonization stages was impaired in mlo colonized plants, highlighting the importance of the early biotrophic growth phase for S. indica root colonization. In contrast, the arbuscular mycorrhizal fungus Funneliformis mosseae displayed a similar colonization morphology on mutant and wild type plants. However, the frequency of mycorrhization and number of arbuscules was higher in mlo-5 mutants. These findings suggest that MLO differentially regulates root colonization by endophytic and AM fungi.